Mining and water enclosures in the Andean Páramo - López Terán, Héctor (2022)
This paper analyzes the water appropriation and concentration in the extraction of mineral deposits in the Andean Páramo. Behind the process of territorial dispossession lies the appropriation, concentration, and delimitation of water used for mineral extraction that restricts and prevents its flow for everyday activities -material and symbolic- aimed at production and consumption. In this sense, the analysis exposes the underlying control and domination over water in the process of dispossession caused by mining activity, in the Andean Páramo, as a way of usurping the common good and imposing the hegemonic social metabolism in terms of capital accumulation and opposing the means and ways of life of the communities linked to the páramo and water.